2D‐Layered Manganese Perovskite with High Mobility. (22nd November 2022) - Cai, Yangyang; Yan, Siyu; Du, Xinran; Lin, Tingting; Lin, Yue‐jian; Qiu, Longzhen; Wang, Weizhi
Abstract: 2D perovskite is an organic–inorganic hybrid material with good photoelectric properties, generally prepared by using organic groups as isolation molecules. In this study, using manganese chloride and potassium halide as raw materials, all‐inorganic 2D lead‐free perovskites are prepared by the Bridgeman melting and cooling method. Different from the 2D perovskites synthesized by organic spacer molecules, the prepared all‐inorganic 2D perovskites have smaller layer spacings and good crystallization performance due to the use of potassium halide as spacer molecules. They are direct bandgap semiconductors and their energy bandgaps are tuned by the different types of potassium halides. High degree orientation crystal thin films with (001) lattice plane parallel to silicon wafer substrate are prepared by double‐source evaporation. The physical morphology of the films is characterized by grazing angle X‐ray diffraction, transmission electron microscopy, and electron diffraction. The field effect transistors prepared from these 2D films show excellent electronic characteristics. The mobility of the optimized device is ≈24 cm 2 v −1 s −1 and the on/off ratio reaches 10 5 . This study reveals the potential of lead‐free manganese 2D perovskite as a high‐performance perovskite field effect transistor. Abstract : The successfully synthesized lead‐free 2D manganese‐based (Mn‐based) all‐inorganic perovskite exhibits high pure crystal with a high carrier transport performance. After optimization, the maximum hole mobility of 2D perovskite field effect transistor (PeFETs) is 24 cm 2 V −1 s −1, and the on/off ratio is 10 5 surpassing all reported PeFETs.